For this case, we have the following quadratic equation:
![16x ^ 2 + 24x + 5 = 5\\16x ^ 2 + 24x + 5-5 = 0\\16x ^ 2 + 24x = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/2yhll5g4wrqan1ppwj4rznejgkk1qx43go.png)
If we divide between 4 on both sides to simplify we have:
![4x ^ 2 + 6x = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/2zlq2w7j2fy5twd52lp8dk8ufplyynic2i.png)
This equation is of the form:
![ax ^ 2 + bx + c = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/sbletey3gjlyp38ihwqyczkdpf2s5u0sfw.png)
Where:
![a = 4\\b = 6\\c = 0](https://img.qammunity.org/2020/formulas/mathematics/high-school/hdhigk2udddyxhlr7svdbm1w8lfko6nqa8.png)
Its roots are given by:
![x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}\\x = \frac {-6 \pm \sqrt {6 ^ 2-4 (4) (0)}} {2 (4)}\\x = \frac {-6 \pm \sqrt {36}} {8}\\x = \frac {-6 \pm6} {8}](https://img.qammunity.org/2020/formulas/mathematics/high-school/xtq5e79b3re1xbmyff1y1y0y4vwu6w4q2p.png)
So, we have two roots:
![x_ {1} = \frac {-6 + 6} {8} = 0\\x_ {2} = \frac {-6-6} {8} = - \frac {12} {8} = - \frac {3} {2}](https://img.qammunity.org/2020/formulas/mathematics/high-school/u7o918jctxr9ncx8drk5bn1nnsbo4c3qy9.png)
Answer:
The roots are:
![x_ {1} = 0\ and\ x_ {2} = - \frac {3} {2}](https://img.qammunity.org/2020/formulas/mathematics/high-school/osti0qpuxe9rrl0ccu40g2z7oimr1o6tkh.png)
None of the options given are solution